Pengembangan Buku Ajar Keterampilan Dasar Mengajar Berbasis Sains Teknologi Masyarakat pada Program Studi Pendidikan Biologi IKIP Budi Utomo Malang - As'ad Syamsul Arifin; Trio Ageng Prayitno (IKIP Budi Utomo Malang, 2016)
The Basic Process of Learning Biology Lecture Course Biology Education Budi Utomo IKIP Malang expected to facilitate the prospective teachers who have professional competence and pedagogy. The process of course are done not much use of learning resources that can stimulate students in order to be sensitive to the problems in society and are able to integrate between science by technological development. Thus, a new innovation that is required one of which develop teaching materials science technology-based society. Learning materials developed only limited subject matter skills open and close the lesson of biology. Teaching material development model of open and closed development model is a biology lesson Thiagarajan 1974: consists of defne, design, develop, and disseminate (special stage is not yet implemented). Technology community science was declared valid. In conclusion, the material taught on the subject of open and close skills lessons of biology-based technology the community science was developed can be used in the process of learning basic biology lectures.